2011
DOI: 10.1080/02673843.2011.9748054
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Narratives: LGBT Transitions and Identities in Malta

Abstract: This article considers narratives of transition experiences of a group of Lesbian, Gay, Bisexual and Transgender (LGBT) young people in Malta. The article draws on Coffman's concept of stigma and uses this to explore transitions in a society that retains some traditional characteristics, particularly the code of honour and shame, although mediated by aspects of modernity. Interviews were undertaken with 15 young people with the goal of producing narratives. The article analyses the experience of stigma, its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…The findings indicate that parents had internalized a hetero- culine privileges as a response to "social difficulties not encountered by heterosexual youth" [25]. Stigma and prejudice are more associated with sexual minority youth than with heterosexual individuals [26].…”
Section: Discussionmentioning
confidence: 87%
“…The findings indicate that parents had internalized a hetero- culine privileges as a response to "social difficulties not encountered by heterosexual youth" [25]. Stigma and prejudice are more associated with sexual minority youth than with heterosexual individuals [26].…”
Section: Discussionmentioning
confidence: 87%
“…Esta pesquisa teve como objetivo analisar as estratégias utilizadas por gays e lésbicas para evitar ou minimizar o estigma nos espaços de trabalho. Para tanto, foi utilizada a teoria do estigma de Goffman (1988), bem como contribuições de diversos autores que retomam Goffman na atualidade (Adams, 2010;Beatty & Kirby, 2006;Berkley, Beard & Daus, 2018;Bradford & Clark, 2011;Clair, Beatty & Maclean, 2005;Herek, 2004;Ragins, Singh & Cornwell, 2007) e outros que buscam incorporar suas análises a fenômenos sociais contemporâneos, tais como as redes sociais (Devito, Walker & Birnholtz, 2018;Duguay, 2016;Owens, 2016). Em virtude dos esforços destes e de outros autores, há mais de quatro décadas as reflexões trazidas por Goffman (1988) permanecem vivas e continuam produzindo intenso debate no atual universo acadêmico.…”
Section: -21unclassified
“…Research by Bradford and Clark (2011) has shown that globalization shapes and nurtures youth in their engagement with adulthood. Emphasizing the many ways modernity and tradition intersect, Bradford and Clark (2011) argue that despite the prevailing forces of globalization that put youth at the centre of discussion, aspects of tradition continue to shape lived experience.…”
Section: Introductionmentioning
confidence: 99%
“…Emphasizing the many ways modernity and tradition intersect, Bradford and Clark (2011) argue that despite the prevailing forces of globalization that put youth at the centre of discussion, aspects of tradition continue to shape lived experience. Globalization, rather than being totalizing and universal, is played out in particular, local and nuanced ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation